The Relationship Between Self-Esteem and Cyberbullying Behavior of Muslim Students on Social Media - Akhyar, Yundri (Sekolah Tinggi Agam Islam Sumatera Medan, 2024)
Low self-esteem can lead to negative compensatory behaviors, while high self-esteem can lead to online aggression. These behaviors are contrary to Islamic values that promote morals. This study examines the relationship between self-esteem and cyberbullying behavior of Islamic students. This study aims to analyze the relationship between self-esteem and cyberbullying behavior among Muslim students in Islamic universities on social media platforms. A descriptive-correlational quantitative survey approach was used to collect data from a sample of 295 students. Pearson correlation analysis was conducted to assess the relationship between self-esteem and digital bullying behavior. The findings showed a strong positive correlation (r=0.724) between self-esteem and bullying behavior on social media, with a significance value of 0.000<0.05, indicating this relationship is statistically significant and very strong. The findings also indicate that decreased levels of self-esteem are associated with increased incidence of cyberbullying behavior. This study provides implications for increased understanding of cyberbullying in Islamic higher education settings. The findings guide the creation of focused initiatives, policies, and additional scientific studies targeting the reduction of cyberbullying. Given its emphasis on different demographics, this study is important because it provides a new angle in a broader research domain.